« C’est dangereux ! » L’accès à l’espace public des femmes roms en situation de vulnérabilité résidentielle restreint par les violences de genre et les violences racistes - Emma Peltier (Genre, Sexualité et Société)
This paper looks into the city access of roma women in precarious living conditions. Its aim is to understand how anti-roma racism and gender shape access to public space. Two spatial practices are studied: begging and daily mobility. The methodology is consisting of long term observations and interviews. I show that living in a slum exposes to gender and racist based violences. In response women use tactics like clothing, avoiding night, being accompanied. Finally begging and walking through the forest are more likely to expose to violences. It leads some of them to fall back on domestic space.